Stable water isotope data 2021-2023 from Lobor village (near Zlatar town) - Briški, Maja; Pavić, Mirja; Borović, Staša; Pola, Marco (In: Briški, M et al. (2023): Stable water isotope data (δ18O and δ2H) of monthly precipitation from 2021 to 2023 (NW Croatia) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.961245, 2023)
Measured values of δ18O and δ2H, associated d-excess values, and amount of collected precipitation from Lobor village, near Zlatar town
Keywords: deuterium; deuterium excess; local meteoric water line; precipitation isotopes; stable water isotopes